The Role of Islamic Religious Education in Shaping Anti-Hoax Attitudes and Wise Digital Literacy in STITMA Yogyakarta Female Students - Nayaka Nafisa Ahmad; Warni Mukti; Yumna Alya Hariyadhi; Widyaningtyas Kusuma Wardani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) in shaping anti-hoax attitudes and wise digital literacy among female students at STITMA Yogyakarta. This study uses a qualitative approach with case study and phenomenology methods. Data were collected through in-depth interviews and observations of female students in the Islamic Religious Education Study Program, supported by library data as secondary sources. The results show that Islamic Religious Education plays a significant role in shaping anti-hoax attitudes through the internalization of Islamic values, particularly tabayyun, the prohibition of slander and gossip, trustworthiness, and moral responsibility in digital media. These values encourage female students to be critical, verify information, and refrain from spreading unconfirmed information, including religious hoaxes. However, this study also found challenges in the form of the rapid flow of digital information and limited critical digital literacy skills. Therefore, strengthening digital literacy based on Islamic Religious Education values through contextual learning and applicable educational programs is an important requirement in building ethical and responsible digital behavior.